INTERACTION OF POWER AND SOCIETY WITHIN THE FRAMEWORK OF THE ASSOCIATION AGREEMENT BETWEEN UKRAINE AND THE EU AND EASTERN PARTNERSHIP POLICY PAPERS - Vnuchko (Внучко Світлана Миколаївна), Svitlana (Politology bulletin, 2019)
Communication of public authorities and society, in particular, public authorities and separate social groups, is an important component of the political and managerial practice of modern society.The world practice shows that effective communication between these actors provides citizens with free access to information, improves the efficiency of government and local self-government bodies, and creates a favourable environment for business development, which in turn serves as the basis for economic stability and the engine of the country’s social and economic development.In the conditions of the development of the information society, new models, mechanisms, platforms of relations and communication between the authorities and the public are emerging. The constructive interaction between power structures and civil society organizations, with a «feedback» component, will contribute to meeting the needs and interests of citizens and strengthening the credibility of both power structures and civil society institutions. Moreover, it will improve the status of Ukraine at the international level by ensuring compliance with the Association Agreement and creating the preconditions for Ukraine to achieve the 20 key priorities of the Eastern Partnership 2020. In the future, consideration should be given to this issue in order to deepen, broaden and improve the effectiveness of the communication component of the government bodies and civil society organizations in Ukraine.In the implementation of communication interaction, special attention should be paid to providing a feedback between communicators. After all, it is this component of the communications process that provides interaction and information about the society’s reaction to the results of the implemented decisions.Purpose of the research: to conduct a scientific, theoretical and practical analysis of functioning of the existing in Ukraine communication platforms of civil society organizations and authorities in the framework of the Association Agreement and the Eastern Partnership policy papers.

Взаємодія влади та суспільства, зокрема, органів державної влади та окремих соціальних груп, виступає важливою складовою політичної та управлінської практики сучасного суспільства.Світова практика підтверджує, що ефективна комунікація між органами державної влади та організаціями громадянського суспільства забезпечує громадянам вільний доступ до інформації, підвищує ефективність органів влади, органів місцевого самоврядування та створює сприятливе середовище для розвитку бізнесу, що, в свою чергу, є основою для економічної стабільності та двигуном соціального та економічного розвитку країни.В умовах розвитку інформаційного суспільства України виникають нові моделі, механізми, платформи відносин та комунікації між владою та громадськістю. Конструктивна взаємодія між владними структурами та організаціями громадянського суспільства України зі складовою «зворотного зв’язку» сприятиме задоволенню потреб та інтересів громадян та зміцненню авторитету як владних структур, так і інститутів громадянського суспільства, а також покращить статус України на міжнародному рівні шляхом забезпечення дотримання положень Угоди про асоціацію та створення передумов для досягнення Україною 20 основних пріоритетів Східного партнерства 2020. Саме тому з метою поглиблення, розширення та підвищення ефективності комунікаційної складової органів державної влади та організацій громадянського суспільства в Україні дане питання потребує додаткової уваги.При здійсненні комунікаційної взаємодії особливу увагу слід приділяти наданню зворотного зв’язку між комунікаторами. Зрештою, саме ця складова комунікаційного процесу забезпечує взаємодію та надання інформації про реакцію суспільства на прийняті рішення.Мета дослідження: провести науковий, теоретичний та практичний аналіз функціонування існуючих в Україні комунікаційних платформ органів державної влади та організацій громадянського суспільства в рамках Угоди про асоціацію та програмних документів Східного партнерства.
ВЗАЄМОДІЯ ВЛАДИ ТА СУСПІЛЬСТВА В РАМКАХ УГОДИ ПРО АСОЦІАЦІЮ МІЖ УКРАЇНОЮ ТА ЄС ТА ПРОГРАМНИХ ДОКУМЕНТІВ СХІДНОГО ПАРТНЕРСТВА
Keywords: communication; interaction of government and society; business associations; civil society organizations; Eastern Partnership; комунікація; взаємодія влади і суспільства; бізнес-асоціації; організації громадянського суспільства; Східне Партнерство